Correlation of structural and chemical characteristics with catalytic performance of hydrotalcite-based CuNiAl mixed oxides for SO2 abatement - Zhao, L.; Li, Xin Yong; Zhao, J. (2013)
A series of flower-like hydrotalcite-based CuNiAl mixed oxides with high surface area were synthesized by urea hydrolysis approach, and employed for SO2 abatement. These catalysts were investigated in detail by means of thermogravimetric analysis (TGA), X-ray diffraction (XRD), scanning electron microscopy (SEM), energy-dispersive spectrometry (EDS), nitrogen adsorption, Fourier transform infrared spectroscopy (FTIR), electron paramagnetic resonance (EPR), UV-vis diffuse reflectance spectroscopy (UV-vis DRS), X-ray photoelectron spectroscopy (XPS) and H2 temperature-programmed reduction (H2-TPR). The results demonstrated that the introduction of copper into NiAlO catalyst could allow substitution of Cu2+ into the NiO lattice to form Cu-Ni solid solutions and induce the appearance of Cu-O pairs. The synergistic effects between Cu and Ni species easily promoted the reduction of the CuNiAlO catalysts and produced more lattice oxygen and then contributed the increasing of catalytic activity for SO2 abatement. Therefore, the CuNiAlO catalysts showed higher catalytic ability than the pristine NiAlO catalyst toward SO2 removal. © 2013 Elsevier B.V..